Mechanical properties of the acrylonitrile- butadienne- styrene (abs) – mixed recycled abs - Mohd Ali Amri, Muhammad Hassan (2012)
Today, plastics are widely used in daily work, because the plastic easy to set up and easy and light to operate. Plastic is also considered a substitute for small items that had been using iron as a material substance. The problem happen when there produce a lot of product to be supplied to the industry. The problems occur when there is a defect in the product or the product does not meet the requirement of customers. The product were rejected and left behind as a waste. The product still can reuse and can be recycled. The objective for this project is to study the mechanical properties of the recycled ABS â mixed- recycled ABS. The ABS was crushed into pallet form to get the recycled material. The recycled material was combined with virgin material. Five samples were needed to make this project. This project was followed an ASTM D638 as a standard .Tests included the tensile stress to determine the strength of the product. After performing the tensile test, the results show that there is resistance on the product that content of 70% Abs and 30% recycled is considered as a percentage of the best in term of tensile strength.